1998
DOI: 10.1093/emboj/17.13.3556
|View full text |Cite
|
Sign up to set email alerts
|

Yeast PKA represses Msn2p/Msn4p-dependent gene expression to regulate growth, stress response and glycogen accumulation

Abstract: Yeast cAMP-dependent protein kinase (PKA) activity is essential for growth and antagonizes induction of the general stress response as well as accumulation of glycogen stores. Previous studies have suggested that the PKA effects on the two latter processes result in part from transcription repression. Here we show that transcription derepression that accompanies PKA depletion is dependent upon the presence of two redundant Zn2+-finger transcription factors, Msn2p and Msn4p. The Msn2p and Msn4p proteins were sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
360
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(386 citation statements)
references
References 43 publications
25
360
1
Order By: Relevance
“…A recent report suggests that Yak1 phosphorylates and thereby activates Msn2 through a still unknown mechanism, which apparently does not implicate the control of Msn2 subcellular localization (Lee et al 2008a). Since the YAK1 gene itself is induced by Msn2/4, this would generate a positive feedback loop (Smith et al 1998). In the same study, Yak1 was also found to stimulate the activity of Hsf1, another transcriptional activator of stress response genes that was recently shown to be under negative control of PKA (Hahn et al 2004;Ferguson et al 2005;Lee et al 2008a).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report suggests that Yak1 phosphorylates and thereby activates Msn2 through a still unknown mechanism, which apparently does not implicate the control of Msn2 subcellular localization (Lee et al 2008a). Since the YAK1 gene itself is induced by Msn2/4, this would generate a positive feedback loop (Smith et al 1998). In the same study, Yak1 was also found to stimulate the activity of Hsf1, another transcriptional activator of stress response genes that was recently shown to be under negative control of PKA (Hahn et al 2004;Ferguson et al 2005;Lee et al 2008a).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…Two of those are the transcription factors Msn2 and Msn4, which mediate the transcription of the so-called stress response element (STRE)-controlled genes (Estruch and Carlson 1993;Martinez-Pastor et al 1996;Schmitt and McEntee 1996). STRE genes are involved in a wide variety of processes, including protection against diverse types of stress such as heat, oxidative and osmotic stress, carbohydrate metabolism and growth regulation (Mai and Breeden 1997;Moskvina et al 1998;Smith et al 1998;Gasch et al 2000). Msn2 and Msn4 are inhibited by PKA and, notably, deletion of both MSN2 and MSN4 rescues the lethality of a tpk null strain (Boy-Marcotte et al 1998;Smith et al 1998).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The fast activation of the Ras-cAMP pathway triggered by glucose addition results in mobilization of storage carbohydrates (Francois, Villanueva, & Hers, 1998;Kraakman et al, 1999;Smith, Ward, & Garrett, 1998;Van der Plaat, 1974), such as glycogen, and increased heat-shock sensitivity, partly mediated by the rapid shutdown of genes containing STRE elements in their promoters (Moskivna, Schuller, Mauer, Mager, & Ruis, 1998;Ruis & Schuller, 1995). Stp1 expressing cells growing on synthetic media supplemented with a non-fermentable carbon source, accumulate higher levels of intracellular glycogen than their wild-type counterparts.…”
Section: The Phenotype Of Cells Expressing Stp1 Is Consistent With Amentioning
confidence: 99%
“…This effect of Ras underlies most, if not all of Ras-induced phenotypes in yeast (Sass et al, 1986;Smith et al, 1998;Stanhill et al, 1999).…”
Section: Introductionmentioning
confidence: 99%